Factors Influencing Student Motivation in English for Specific Purposes at Eastern Indonesian Universities - Lapele, Fitria; Aman, Aman; Putro, Nur Hidayanto Pancoro Setyo (Institut Agama Islam Negeri Madura, 2025)
Motivation to learn English is essential for university students worldwide, as it impacts engagement and success in both general and specific academic contexts. However, prior research has seldom focused on motivation in English for Specific Purposes (ESP), especially in particular fields or majors, and is particularly limited in universities in Eastern Indonesia. This study aims to explore the factors of motivation among students in ESP programs and to identify which are most and least effective in supporting their learning. 150 students from universities in Eastern Indonesia participated in this study. Employing both qualitative and quantitative data collection methods, students completed a quantitative questionnaire on their learning motivation, with data analyzed using SPSS 27. Additionally, qualitative data were collected through focus group interviews with 16 participants who had completed ESP courses, providing further insights into their opinions on ESP learning. The findings reveal that students are highly motivated by factors such as encouragement to communicate and collaborate with peers, clarity and ease of classroom instructions, and fairness and consistency in assessments. Moreover, the lecturer’s role in creating a positive classroom atmosphere was noted as a significant motivational factor. However, a lack of alignment between classroom activities and students’ specific fields often leads to disengagement. These results offer valuable references for ESP lecturers seeking to adopt practices that better motivate students, particularly by emphasizing career relevance and supportive learning environments.